Respuesta :

ANSWER

[tex]x - 4 = 0 \: or \: x + 2 = 0[/tex]

EXPLANATION

Given:

[tex](x + 1)(x - 3) = 5[/tex]

Expand:

[tex] {x}^{2} - 3x + x - 3 = 5[/tex]

[tex] {x}^{2} - 2x - 3 = 5[/tex]

Equate everything to zero.

[tex] {x}^{2} - 2x - 3 - 5 = 0[/tex]

[tex] {x}^{2} - 2x - 8 = 0[/tex]

Split the middle term;

[tex] {x}^{2} + 2x - 4x - 8 = 0[/tex]

Factor;

[tex] x(x + 2) - 4(x + 2) = 0[/tex]

[tex](x - 4)(x + 2) = 0[/tex]

Use zero product property,

[tex]x - 4 = 0 \: or \: x + 2 = 0[/tex]

Answer:

Choice C is correct.

Step-by-step explanation:

We have given the equation:

(x+1)(x-3)=5

We have to choice the correct option.

Product property states that:

if ab=0 then a=0 or b =0.

(x+1)(x-3)=5

x²-2x-3 = 5

x²-2x-3-5 = 0

x²-2x-8 = 0

factorize the above equation we get,

x²+2x-4x-8=0

x(x+2)-4(x+2) = 0

(x+2)(x-4) = 0

Using zero product property we get,

(x+2) = 0       or      (x-4) = 0

So, choice C is correct.